2011
DOI: 10.1007/s11581-011-0533-7
|View full text |Cite
|
Sign up to set email alerts
|

Point defect diagrams for pure and doped nickel oxide $$ {\hbox{N}}{{\hbox{i}}_{{1} - \delta }}{\hbox{O}} $$ in the temperature range of 1,173–1,673 K (II)

Abstract: The point defect diagrams in nickel oxide Ni 1Àd O, pure and doped with M 3+ and M + metal ions, taking into consideration all of the types of defects in the cation sublattice, are presented in this work. A new method was used for the calculations of the diagrams. This method is based on the derived relations between the standard Gibbs energies of the formation of nickel vacancies and the intrinsic ionic and electronic defects. It also uses the experimental values of the deviation from the stoichiometry. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The points ((□) vac) denote the values obtained for the model of the structure of simple defects (Stokłosa, 2011b). As shown in Figure 2, the introduction of defect clusters into the model of the structure of defects does not change the adjusted value of o V " Ni ΔG .…”
Section: δGmentioning
confidence: 99%
See 4 more Smart Citations
“…The points ((□) vac) denote the values obtained for the model of the structure of simple defects (Stokłosa, 2011b). As shown in Figure 2, the introduction of defect clusters into the model of the structure of defects does not change the adjusted value of o V " Ni ΔG .…”
Section: δGmentioning
confidence: 99%
“…In the previous work (Stokłosa, 2011b), the calculations of the diagrams of concentrations of point defects in Ni 1-δ O were presented, assuming in the first approximation the presence of nickel vacancies and interstitial ions with the highest ionization degree and lower ionization degrees. As a result of these calculations, it has been found that in the temperature range of 1273-1673 K, taking into account only " Ni V and…”
Section: Concentrations Of Simple Defects and Defect Clusters In Ni 1mentioning
confidence: 99%
See 3 more Smart Citations